JURIDICAL ANALYSIS OF CRIMINAL SANCTIONS AGAINST INTERMEDIARIES IN NARCOTICS SALES (A STUDY OF DECISION NUMBER 395/PID.SUS/2025/PN STB) - Muhammad Imanuddin; Muhammad Ridwan Lubis (CV. Barokah Publsiher, 2026)
Based on the results of the study, it shows that the criminal law regulations for intermediaries in narcotics sales are regulated in Law Number 35 of 2009 concerning Narcotics, namely Article 114, the threat of imprisonment of at least 5 years and a maximum of 20 years, Article 119, the threat of imprisonment of at least 4 years and a maximum of 12 years, Article 124, the threat of imprisonment of at least 3 years and a maximum of 10 years. Proof of the elements of the crime committed by the accused intermediary for narcotics sales in Decision Number 395 / Pid.Sus / 2025 / PN Stb is appropriate because it has used two minimum pieces of evidence as regulated in Article 183 of the Criminal Procedure Code. The legal analysis of the punishment for the perpetrators of intermediary sales of narcotics in Decision Number 395 is quite fair, namely defendants I and III were sentenced to 10 years in prison, defendant II because he had never been imprisoned received leniency with a prison sentence of 9 years.